TINDAK TUTUR EKSPRESIF DALAM UNGGAHAN TIKTOK TENTANG DEEP LEARNING - Sya'adatul Hayat; Prayitno , Harun Joko (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
TikTok has emerged as an educational discourse space that reflects public responses to the concept of deep learning within instructional contexts as a pedagogical approach. This study aims to describe the forms and meanings of expressive speech acts found in users’ comments on TikTok content related to deep learning, while also linking them to the values of mindful, meaningful, and joyful learning. The data consist of 50 expressive utterances collected from user comments during the period of January to March 2025. This research employs a descriptive qualitative approach using an extralingual equivalent method to relate linguistic forms to their underlying social and digital contexts. The findings reveal a range of expressive speech acts, including criticism (32%), complaints (26%), praise (18%), expectations (10%), agreement (8%), affirmation (4%), sarcasm (2%), and expressions of gratitude (2%). Criticism and complaints reflect the value of mindful learning, as they demonstrate users’ critical awareness of the gap between theoretical concepts and actual classroom practices. Praise and gratitude represent the value of joyful learning through expressions of appreciation and positive learning experiences. Meanwhile, expectations and agreement indicate the value of meaningful learning, as they convey interpretations of the relevance and benefits of deep learning. This study contributes theoretically to the field of digital pragmatics and practically provides insight into public responses toward educational communication on social media platforms.